Splitting the eggs methods: Comparison of egg survivorship between styrofoam and open area nests for Penang Island and turtle conservation - Mohd Sarahaizad, Sarahaizad; Mohd Sah, Shahrul Anuar; Jalal, K. C. A. (Malaysian Society of Applied Biology, 2017)
This research paper reports the observation of successful hatching comparing Styrofoam and Open Area nest. Splitting the eggs method was studied using green turtle (Chelonia mydas) clutch size whereby they were divided equally and incubated in two nest plots (Styrofoam and Open Area). The aim of this study is to test the rate of hatching success between the two nest plots, as well as to measure the hatchling morphological characteristics. Results showed that eggs incubated in Open Area nest produced slightly higher hatching success (81.16%), than Styrofoam nest (74.31%). Mean incubation period of Open Area nest was 54.1 days, while in Styrofoam nest was 56.3 days, as low temperature slows down the time of hatching. Hatchling from Open Area nest had larger straight carapace length measurement (mean HSCL=45.89 mm) than hatchling from the Styrofoam nest (mean HSCL=45.23 mm). In contrast, emergence success in Styrofoam nest shows better hatchling emergence. This research is important, as we need to know the rate of hatching success when incubated either in Open Area or Styrofoam nest. Splitting the eggs method shows that Open Area nest produced a good rate of hatching success and hatchling morphological characteristics. It is recommended to further this study to test the hatchling physical performance between Styrofoam and Open Area nest, as high energy reserved within individual’s hatchling body does impact their longer survival to face the ocean’s predator and also for a greater fitness.